Global Financial Stability Report, October 2007 : Financial Market Turbulence Causes, Consequences, and Policies. (Global Financial Stability Report; Global Financial Stability Report ;, 2007)
Published twice yearly, the Global Financial Stability Report (GFSR) was created to provide a more frequent assessment of global financial markets by the IMF and to address emerging market financing in a global context. It provides timely analysis of developments in both mature and emerging market countries and seeks to identify potential fault lines in the global financial system that could lead to crisis. The GFSR aims to deepen its readers' understanding of global capital flows, which play a critical role as an engine of world economic growth. Of key value, the report focuses on current conditions in global financial markets, highlighting issues of financial imbalances, and of a structural nature, that could pose risks to financial market stability and sustained market access by emerging market borrowers.